Small cell osteosarcoma of the rib: An exceptional localization. Issue 9 (23rd September 2022) - Abid, Walid; Triki, Meriam; Hlima, Ghassen Ben; Chaari, Zied; Hentati, Abdessalem; Frikha, Imed
Abstract: Small cell osteosarcoma is a rare sub‐type of osteogenic malignant tumors. Rib localization is uncommon. Histological examination is an important step to make the difference with similar tumors like Ewing's sarcoma. Surgical resection is the unique curative treatment. The prognosis remains poor even with adjuvant treatment. Abstract : Small cell osteosarcoma is a rare sub‐type of osteogenic malignant tumors. The difference with other types is retained on histological characteristics. A wrong diagnosis may cause a delay in the management of this type of cancer, mainly on surgical resection which is the unique curative treatment.